2022
DOI: 10.1007/s11548-022-02680-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical reporting for laparoscopic cholecystectomy based on phase annotation by a convolutional neural network (CNN) and the phenomenon of phase flickering: a proof of concept

Abstract: Purpose Surgical documentation is an important yet time-consuming necessity in clinical routine. Beside its core function to transmit information about a surgery to other medical professionals, the surgical report has gained even more significance in terms of information extraction for scientific, administrative and judicial application. A possible basis for computer aided reporting is phase detection by convolutional neural networks (CNN). In this article we propose a workflow to generate operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Familiarity with the SR components and optimisation of reports with auto-population features may further expedite data entry [ 2 ]. Bertlet et al demonstrated the potential to utilise machine learning and convolutional neural networks to populate SR from the operative video [ 19 ]. Additionally, cost savings related to reduced typing time (if reports were dictated) may be achieved with SR [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Familiarity with the SR components and optimisation of reports with auto-population features may further expedite data entry [ 2 ]. Bertlet et al demonstrated the potential to utilise machine learning and convolutional neural networks to populate SR from the operative video [ 19 ]. Additionally, cost savings related to reduced typing time (if reports were dictated) may be achieved with SR [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%